Comparative analysis and supragenome modeling of twelve Moraxella catarrhalis clinical isolates - Davie, Jeremiah J (BioMed Central, 2011)
BACKGROUND: M. catarrhalis is a gram-negative, gamma-proteobacterium and an opportunistic human pathogen associated with otitis media (OM) and exacerbations of chronic obstructive pulmonary disease (COPD). With direct and indirect costs for treating these conditions annually exceeding $33 billion in the United States alone, and nearly ubiquitous resistance to beta-lactam antibiotics among M. catarrhalis clinical isolates, a greater understanding of this pathogen's genome and its variability among isolates is needed. RESULTS: The genomic sequences of ten geographically and phenotypically diverse clinical isolates of M. catarrhalis were determined and analyzed together with two publicly available genomes. These twelve genomes were subjected to detailed comparative and predictive analyses aimed at characterizing the supragenome and understanding the metabolic and pathogenic potential of this species. A total of 2383 gene clusters were identified, of which 1755 are core with the remaining 628 clusters unevenly distributed among the twelve isolates. These findings are consistent with the distributed genome hypothesis (DGH), which posits that the species genome possesses a far greater number of genes than any single isolate. Multiple and pair-wise whole genome alignments highlight limited chromosomal re-arrangement. CONCLUSIONS: M. catarrhalis gene content and chromosomal organization data, although supportive of the DGH, show modest overall genic diversity. These findings are in stark contrast with the reported heterogeneity of the species as a whole, as wells as to other bacterial pathogens mediating OM and COPD, providing important insight into M. catarrhalis pathogenesis that will aid in the development of novel therapeutic regimens.